PENGARUH MODEL PEMBELAJARAN EXPERIENTAL LEARNING TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS IV SDN 28 BONTOMACINNA KABUPATEN BULUKUMBA - Dea Novita; M. Agus; Syekh Adiwijaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The study aims to find out the impact of experiential learning learning models on the poetry writing skills of students of SDN 28 Bontomacinna district of Bulukumba. This type of research uses a type of quantitative research. The research was carried out at SDN 28 Bontomacinna district of Bulukumba. The subjects in this study are students of class IV A and IV B. Data collection techniques using observation, testing and documentation techniques. Data analysis techniques use descriptive analysis and analysis of inferential data. Research results are analyzed using descriptional and inferential statistics. Descriptive is used to describe the implementation of the learning process and student poetry writing skills, while inferential uses the t test to test the hypothesis. Observations of the learning process showed an increase from effective (78,57%) at the first meeting to highly effective (89.28%) on the second meeting.The pretest analysis showed that the average student poetry skills in the experimental class was 55.33 and in the control class 55.00, both of which were in the fairly skilled category. After the treatment, the posttest showed a significant improvement with the average experimental grade 83.00 (skilled category) and control class 63.67 (kategori cukup terampil). N-Gain test results showed an improvement in poetry writing skills in the middle category with an average score of 0.6159 for the experimental class.The results of the independent sample t-test showed significant differences in poetry skills between the experimental class and the control class after given treatment (t-count = 6,769 > t-table = 2,048, p < 0,05).From the results of this study, it can be concluded that the learning model Experiential Learning has a significant influence on the improvement of poetry writing skills of students of the IV grade SDN 28 Bontomacinna, Bulukumba district.